MANAJEMEN SARANA PRASARANA DALAM MENINGKATAN KOMPETENSI SISWA SMK DI KOTA BANDUNG - Supriatna, endang (PT. Solusi Komunikasi Terapan, 2023)
Low in the student’s practice score, could reach low of student compatitative ability in Bandung, that impact from management infrastructure uncompleted. The research purpose for knowing illustration of planning, implementation, evaluation, problem and solve the problem faced in management infrastructure to increase students of vocational high school competence in Bandung. The research method used is descriptive method with a qualitative approach, data obtained through observation techniques, documentation studies, and interview. The conclusion of the research results is that infrastructure is one of the important and main resources in improving student competence in schools. The availability of complete and good educational infrastructure and management according to management standards will provide positive motivation to vocational students, so that learning activities will be more interesting and really help students in compensating for the obstacles they have, so that students can learn optimally and and creative.